1993
DOI: 10.1093/hmg/2.9.1413
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype diversity in the human red and green opsin genes: evidence for frequent sequence exchange in exon 3

Abstract: We studied polymorphisms in the coding sequences of the human red and green opsin genes of 133 Caucasian males. Eleven polymorphic sites were discovered in the red opsin gene, seven of which were in exon 3, three in exon 4 and one in exon 5. Polymorphisms at 8 of these sites resulted in amino acid substitutions which generated a total of 18 unique red opsins in the population. The substitutions at three (S180A, I230T, and A233S) of the 8 sites involve hydroxyl-bearing to non-polar amino acid residues, and are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 0 publications
1
76
0
Order By: Relevance
“…The sequences of the red and green genes are very similar to each other, indicating that the two genes are undergoing concerted evolution. There are a very limited number of fixed differences between the two genes (Nathans et al 1986;Winderickx et al 1993;Hayashi et al 2001), at least three of which are known to be responsible for the difference in color sensitivity. Particularly, two of the three are closely located in exon 5 (amino acids 277 and 283), and these two account for .80% of the functional difference (measure by l max , a peak value of the light absorption spectrum) between the red and green pigments (Neitz et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The sequences of the red and green genes are very similar to each other, indicating that the two genes are undergoing concerted evolution. There are a very limited number of fixed differences between the two genes (Nathans et al 1986;Winderickx et al 1993;Hayashi et al 2001), at least three of which are known to be responsible for the difference in color sensitivity. Particularly, two of the three are closely located in exon 5 (amino acids 277 and 283), and these two account for .80% of the functional difference (measure by l max , a peak value of the light absorption spectrum) between the red and green pigments (Neitz et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Neitz & Jacobs, 1986;J. Neitz, M. Neitz, & Jacobs, 1993;Winderickx, Battisti, Hibiya, Motulsky, & Deeb, 1993).…”
Section: The Biological Basis Of Trichromacymentioning
confidence: 99%
“…Although larger sample sizes are needed to accurately assess the population frequency of the serine-180 shift versus the alanine-180 shift, some investigations suggest that the general Caucasian populationshows a~56% occurrence for the "normal" serine 180 and a~44% occurrence of a polymorphic mutation alanine 180 for the red pigment gene. By comparison, the frequency of occurrence for the green pigment gene is~96% "normal" alanine 180 and~4% polymorphic serine 180 (Winderickx et al, 1993). Asenjo et al (1994), M. Neitz and J. , and , show that the serine amino acid at codon 180 is primarily linked to the normal red gene, whereas the presence of alanine at codon 180 can indicate the presence of a polymorphic (shifted) red photopigmentgene, the presence of a normal green gene, or the presence of both a shifted red and a normal green gene.…”
Section: Genetic Structure Underlying Visual Pigment Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…This pattern has been demonstrated, for example, in the rDNA gene family (Arnheim et al 1980) and visual pigment genes in Old World monkeys (e.g., Winderickx et al 1993;Zhou and Li 1996). Conversely, it has been suggested that gene conversion may generate diversity among paralogs through reassortment of genetic variation in the major histocompatibility complex gene family (e.g., Weiss et al 1983;Ohta 1997;Martinsohn et al 1999).…”
mentioning
confidence: 99%